Modelling of the pore pressure response in sediments due to the movements generated by seismic waves, by means of the spectral element method (2019)
"Earth's materials such as rocks and soil are not a completely homogeneous medium, they have discontinuities inside their inner structure known as pores or voids, which typically are filled with a fluid. The pressure exerted by the trapped fluid inside the voids its known as pore pressure. This groundwater pressure within a soil or rock responds to the medium's stress field, following a coupled diffusion-deformation pehomena between the solid part of the system and the fluid one. A well known and effective mechanism that can generate variations on the stress setting along sediments is the cyclical action of earthquakes generated by telluric movements. Usually, soils fail under stress conditions that surpass their bearing capacity, but it is not the only way the sediments can reach failure. When the pore pressure varies at a critical rate or reaches a certain critical value, failure can occur in terms of fracture or soil liquefaction. The last one corresponds to a very hazardous mass movement where the saturated sediments act as a pseudo-liquid material. Therefore, the study of pore pressure variations in saturated soil turns into a relevant topic when treating sediment failure or studying the mechanical response of the porous media. This work describes the process developed to model the pore pressure response in sediments due to the action of seismic waves, by means of the finite element method (FEM). The goal of the project is to analyze the pore pressure diffusion in sediments and how it influences the first stages of soil liquefaction as well as compare the pore pressure response between different sediment models and predict their sensibility to pressure variations and soil failure."--Tomado del Formato de Documento de Grado.